OC-086 Survival Benefit of FDG-Pet Oriented Surgery for Recurrent Colorectal Cancer. (4th June 2013) - Ishikawa, H; Watanabe, A; Mukogawa, T; Nakatani, M; Nishiguchi, Y; Matsusaka, M; Ko, S
Abstract : Introduction: Pivotal treatment for localised recurrent colorectal cancer is surgical resection. Fluorine-18 fluorodeoxyglucose positron emission tomography (FDG-PET) has been accepted as an effective tool to identify disease localizations for patients with known or suspected recurrent colorectal cancer. This study is to analyse the survival benefit of FDG-PET on the diagnosis and indication of surgical intervention for Methods: Consecutive 61 patients, with known or suspected recurrence of colorectal cancer based on elevation of tumour markers or abnormal findings on the follow-up CT image, underwent FDG-PET for 85 times between December 2003 and September 2009. Patients were aged between 39 and 94 years (median 66); 35 were male, 22 were Duke's A or B stage, and 31 had a history of colon cancer. The average period between operation and first FDG-PET was 24 months (range 4–114). Of 61 cases 50 had elevated serum CEA or CA19–9 (82.0%). For each case the diagnosis of FDG-PET image was compared with that of CT image and the final diagnosis. Results: Recurrence developed 2 times in average (range 1–6). Of 61patients five were identified recurrence by FDG-PET solely and indicated operation for 7 times. One of four shows disease-free survival for 70 months after common iliac replacement operation. FDG-PET showed one false – positive and three false – negative findings. Totally, the sensitivity of FDG-PET was 93.3% and its accuracy was 91.8%, whereas those of CT were 85.0% and 83.6%, respectively. Of 61patients 19 had diffused disease spread by FDG-PET findings and were judged as contraindication of operation and the other 42 with localised disease spread received operation for 90 times (liver 28, lung 14, local 37, local with distant meta 5, etc.). Cumulative 1-year and 3-year survival ratios of operation cases after first recurrence were 95% and 80%, whereas, those of contraindication cases were 60% and 25%, respectively. At present, the median survival period after recurrence of operation cases was longer than that of contraindication cases ( 37months v.s. 13months ). Our results suggested that one FDG-PET oriented operation roughly corresponded to one year survival benefit with restart. Conclusion: Conclusion: FDG-PET could identify malignant lesions at earlier stage, and was an effective modality to evaluate not only disease spread but distant metastasis for recurrence of colorectal cancer. In this study, we first concretely demonstrated that FDG-PET oriented surgical indication had survival benefit for recurrent colorectal cancer. Disclosure of Interest: None Declared